PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS TIKTOK PADA MATA PELAJARAN INFORMATIKA - Ayu Lestari; Muhammad Yahya; Abdul Muis Mappaloteng (UNM Journal of Technology and Vocational, 2025)
This study aims to: 1) develop learning media, 2) assess the validity and practicality, and 3) measure the effectiveness of TikTok-based learning media. The research employs the Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The study was conducted at SMK Negeri 2 Luwu with test subjects comprising instrument experts, material and lesson plan experts, learning media experts, and 10th-grade students from the Software Engineering and Mechanical Engineering departments. Data were collected through validation sheets and student response questionnaires. The results indicate that: 1) TikTok-based learning media for the Informatics subject was successfully developed; 2) The media was validated with a validation percentage of 98.5% from instrument experts, 97% from material experts, and 97% from learning media experts; 3) The developed media met the criteria for practicality with positive student responses of 90.27%; 4) The developed media met the criteria for effectiveness, as shown by an improvement in learning outcomes with an average post-test score of 78.57% and an average gain score of 0.55 (moderate category).